2016
DOI: 10.1002/tal.1344
|View full text |Cite
|
Sign up to set email alerts
|

Lateral drift constrained structural optimization of an actual supertall building acted by wind load

Abstract: Recent trends towards constructing taller and increasingly slender buildings imply that these structures are more sensitive to wind excitation. This paper presents a technique for the wind‐resistant optimal design of supertall buildings with a complex structural system including concrete‐filled steel tube columns, shear walls, and various types of beams and columns. In each optimal design cycle, the dynamic wind load acting on a building is transformed into a set of multiple‐oriented equivalent static wind loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The applicability of linear mode shape assumption for HFFB technique has been proved by a number of engineering applications in the past decades. [6,8,12] Equation 5d indicates that based on the assumption of linear mode shape, the modal force can be easily obtained from the measured BBM.…”
Section: Response Computation For a Hffb Wind Tunnel Testmentioning
confidence: 99%
See 3 more Smart Citations
“…The applicability of linear mode shape assumption for HFFB technique has been proved by a number of engineering applications in the past decades. [6,8,12] Equation 5d indicates that based on the assumption of linear mode shape, the modal force can be easily obtained from the measured BBM.…”
Section: Response Computation For a Hffb Wind Tunnel Testmentioning
confidence: 99%
“…Hence, an important purpose of wind tunnel tests, including HFFB tests and wind tunnel tests with synchronous multi‐pressure sensing system (SMPSS), is to provide accurate ESWL to structural engineers for loading combination and structural analysis. For a SMPSS wind tunnel test, the wind‐induced response can be computed precisely using the complete quadratic correlation method, and then, the ESWL can be calculated precisely by means of load‐response correlation method . All equations for these computations are strictly deduced, and it is not necessary to separate the total structural response into background part and resonant part.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] There are several major ways to improve the wind-resistant performance of a tall building after completing its preliminary architectural and structural design, such as by locally changing the building shape to optimize its aerodynamic characteristics, [3,4] by installing damping system to reduce the response to dynamic loads, or by optimizing the cross-sectional sizes of structural members to reduce its response to wind excitations. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Compared with the first two approaches, the structural optimization method does not require any change of the building shape or structural system and any expenses for adding and maintaining any additional damping system, and so the structural optimization method has now been widely accepted by researchers and engineers in the structural design of tall buildings. [5,13,16] Studies [9][10][11][12][13][14][15][16][17] have shown that the constructional material cost of a tall building can be effectively reduced by the structural optimization.…”
mentioning
confidence: 99%